Исследование позднепалеолитической стоянки у с. Синичино - Снежко, И. А. (Давнина. Харківський історико-археологічний щорічник, 2016)
Snezhko L.A. Researches of the Late Paleolithic Camp Near the Sinichino Village: Kharkov Region